PARTICIPATION OF CIVIL SOCIETY INSTITUTIONS IN CIVIL SERVICE COMPETITIONS - Mahnovskyi, Ihor Y.; Stets, Oleh M. (International Journal of Psychosocial Rehabilitation, 2020)
Currently, in Ukraine, attempts of civil society institutions to participate in public problem solving seem to be unsuccessful, including in competitions for vacant civil service posts. Reevaluation of their functional role in the competition is considered to be one of the main tasks of development of democratic governance. The purpose of this article is to determine possible ways to improve efficiency of interaction between Ukrainian civil society institutions and public administration subjects in competitions for vacant civil service posts; to define a single concept of governance humanization and democratization and to offer specific recommendations on reforming citizen participation in competitions for vacant civil service posts in Ukraine. During the research, general and special methods of scientific knowledge were used: system analysis method, dialectical method, formal logical method, and structural functional method, as well as certain empirical methods. The authors came to the conclusion on poor interaction between public administration subjects and civil society institutions in competitions for vacant civil service posts in Ukraine. The positive effect of new forms of public involvement can be improved by promotion of e-participation of citizens in the public administration. Free access to electronic reflection of any public administration subject’s activity is believed to simplify public involvement in making decisions. The results of the research seem to be interesting and useful for national legislators and public administration subjects against actualized tendencies in democratization and humanization of administrative processes. The research subject is considered in Ukraine for the first time and seems to have the prospect of further development.